Custom Paralympic shooting jacket: a single-case product development project - Hobbs, Kayna, author; Morris, Kristen, advisor; Kissell, Kevin, committee member; Kreston, Rosemary, committee member (Colorado State University. Libraries, 2020)
The goal of this research was to develop a custom regulation jacket for a Paralympic Shooting athlete. A six-step design process was implemented to understand the design needs of a Paralympic shooting athlete in their shooting jacket. Data were collected through qualitative research methods in a single-case study design. The participant's design needs in their shooting jacket were framed through Lamb and Kallal's (1992) FEA (functional, expressive, aesthetic) Consumer Needs Model. Three research questions that guided this study were, RQ1) How can weighing of FEA needs, defining design insights, and communication between designer and end user aid in creating high-satisfaction custom sportswear for the single-case participant? RQ2) How can utilization of 3D body scanning and virtual garment simulation technology improve the custom sportswear development process and create high-satisfaction in the end product for the single-case participant? And RQ3) How do functional, expressive, and aesthetic needs (FEA needs) inform the single-case participant's Paralympic Shooting jacket preferences and desires? To address these questions, the researcher used anthropometric body measurements, 3D body scanning, virtual garment simulation technology, and half-scale dress forms to develop the custom shooting jacket throughout the design process. Overall, this research contributes to an understanding of factors and processes needed to develop clothing or sportswear for disabled athletes. The main outcomes of this research are a regulation Paralympic shooting jacket and a new model of apparel needs for disabled athletes called the FEA Model for Disabled Athletes. The model advances theory in the field of apparel design and is a step in the direction of understanding the clothing needs of disabled athletes. This study provides industry and research professionals with best practices when working with these populations and products.
Keywords: design; Paralympic; wheelchair; disability; clothing; sports